Scientific evidence about prevalence falls and associated factors in elderly (Research, Society and Development, 2020)
Objective: to elucidate, through a systematic review, the scientific evidence about the prevalence of falls and the influence of variables associated with them in the elderly. Methods: this is a study of systematic literature review, carried out in the SciELO and BVS databases through controlled descriptors, elderly, associated factors and prevalence, as well as their translations into Spanish and English, according to the DeCS and Mesh, published between 2010 and 2020. Results: We identified a total of 55 factors associated with falls in the elderly, in the studies selected in this review. The prevalence of falls in institutionalized elderly ranged from 15.1% to 100%, with the main associated factors presented: the need for some type of assistance to move around, weakness, balance, gait disorders, mobility disorders and postural control (83%), female gender (50%) and skin color, difficulties in seeing, inadequate environments and associated comorbidities (33%). The prevalence of falls in non-institutionalized elderly people ranged from 10.7% to 59.3%, with the main associated factors: female gender and advanced age (57%), problems related to walking and associated comorbidities (38%) and inadequate environments (33%). Final considerations: Given the above, we can conclude that the main risk factors associated with the risk of falls for the elderly, institutionalized and non-institutionalized, mentioned in the selected studies, form the need for some type of assistance to move around, weakness, balance, disorders of gait, mobility disorders and postural control, female gender, advanced age, skin color, difficulties in seeing, inadequate environments and associated comorbidities.